Electrophysiology Tool Construction. Issue 1 (1st January 2013) - Ide, David
Abstract: This protocol documents the construction of a custom microscope stage system currently in widespread use by a wide variety of investigators. The current design and construction of this stage is the result of multiple iterations, integrating input from a number of electrophysiologists working with a variety of preparations. Thus, this tool is a generally applicable solution, suitable for a wide array of end‐user requirements; its flexible design facilitates rapid and easy configuration, making it useful for multi‐user microscopes, as individual researchers can reconfigure the stage system or have their own readily replaceable stage plates. Furthermore, the stage can be manufactured using equipment typically found in small research machine shops, and by keeping the various parts on hand, machinists can quickly satisfy new requests and/or modifications for a wide variety of applications. Curr. Protoc. Neurosci . 62:6.26.1‐6.26.11. © 2013 by John Wiley & Sons, Inc.